Do Musicians Have Better Mnemonic and Executive Performance Than Actors? Influence of Regular Musical or Theater Practice in Adults and in the Elderly - Groussard, Mathilde (Front Hum Neurosci, 2020)
The effects of musical practice on cognition are well established yet rarely compared with other kinds of artistic training or expertise. This study aims to compare the possible effect of musical and theater regular practice on cognition across the lifespan. Both of these artistic activities require many hours of individual or collective training in order to reach an advanced level. This process requires the interaction between higher-order cognitive functions and several sensory modalities (auditory, verbal, visual and motor), as well as regular learning of new pieces. This study included participants with musical or theater practice, and healthy controls matched for age (18–84 years old) and education. The objective was to determine whether specific practice in these activities had an effect on cognition across the lifespan, and a protective influence against undesirable cognitive outcomes associated with aging. All participants underwent a battery of cognitive tasks that evaluated processing speed, executive function, fluency, working memory, verbal and visual long-term memories, and non-verbal reasoning abilities. Results showed that music and theater artistic practices were strongly associated with cognitive enhancements. Participants with musical practice were better in executive functioning, working memory and non-verbal reasoning, whereas participants with regular acting practice had better long-term verbal memory and fluency performance. Thus, taken together, results suggest a differential effect of these artistic practices on cognition across the lifespan. Advanced age did not seem to reduce the benefit, so future studies should focus on the hypothetical protective effects of artistic practice against cognitive decline.